Ownership structure and debt as corporate governance mechanisms: an empirical analysis for Spanish SMEs - Hernández-Cánovas, Ginés; Mínguez-Vera, Antonio; Sánchez-Vidal, Javier (Journal of Business Economics and Management, 2016)
The purpose of this paper is to analyze the relationship between ownership structure and indebtedness for a sample of 2,544 Spanish small and medium enterprises. A System Generalized Method of Moments methodology is applied to control for the heterogeneity and endogeneity problems. The finding shows a negative effect of several measures of ownership on debt ratio. Therefore, the presence of an individual as main shareholder has a positive effect on debt, while the presence of a corporation as main shareholder exerts a negative influence. As research implications, this paper includes the agency problem based on principal-principal conflicts to explain the capital structure of small and medium enterprises, going beyond traditional principal-agent conflicts. The main practical implications of the paper is that owners who seek equity financing can use the results of this study for understanding better why investors are reluctant to invest in their small and medium enterprises. Policymakers can use the results of this study to develop better policies and to promote better provision of information for all stakeholders. About the contribution of this study, we are not aware of any paper that uses a panel of small and medium enterprises operating in a French-civil law country to examine the relationship between indebtedness and three different proxies of the ownership structure. First published online: 28 May 2014